1999
DOI: 10.1007/s003470050467
|View full text |Cite
|
Sign up to set email alerts
|

Management of submacular hemorrhage by tissue plasminogen activator and SF6 gas injection

Abstract: Toxic and hypoxic damage of foveolar photoreceptors by subretinal hemorrhage can be prevented by early and minimal invasive fibrinolytic therapy. After localization of choroidal neovascularizations, treatment by focal laser coagulation is possible in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…Vitreous hemorrhage rate ranged from 0–45% in group 1 [25,27,28,29,30,31,32,33,34,35,37,38,40,41,42,43],and 0–43% in group 2 [11,12,13,24,44,45 ](table 3). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitreous hemorrhage rate ranged from 0–45% in group 1 [25,27,28,29,30,31,32,33,34,35,37,38,40,41,42,43],and 0–43% in group 2 [11,12,13,24,44,45 ](table 3). …”
Section: Resultsmentioning
confidence: 99%
“…One study employed intravitreal rtPA with and without intravitreal gas injection [28]. Fifteen studies reported intravitreal injection of both rtPA and gas [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]; one of these 15 studies incorporated the results of its own, older article [32,39]. Five studies reported intravitreal rtPA and intravitreal anti-VEGF agents and gas injections [11,12,13,44,45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The technique has since been evaluated, and favourable results have been reported in several published series. [13][14][15] However, most of these studies were observational, with no control group to compare the anatomic and visual outcomes of AMD patients treated by gas displacement with and without t-PA.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure was performed with topical anesthesia, 25-100 μg tPA in 0.1-0.2 ml injected into the vitreous cavity through the pars plana, followed by a 0.3-to 0.4-ml injection of perfluoropropane (C 3 F 8 ) or sulfur hexafluoride (SF 6 ) gas and 24-hour prone positioning. However, subsequent case series from Germany [26][27][28][29][30], Austria [31], China [32], Thailand [33], and Australia [34] using similar techniques were less impressive, with results ranging from 38 to 64% demonstrating a ≥2 ETDRS line gain. Larger series from Asia also included idiopathic polypoidal choroidal vasculopathy, retinal macroaneurysms, and pathologic myopia, although the outcomes were similar to those reported for AMD patients [35,36].…”
Section: Pneumatic Displacementmentioning
confidence: 91%